Altitude training - Karp, J. R. (Techniques Magazine, 2012)
Although many coaches, athletes and TV commentators attribute much of the success of the Kenyan and Ethiopian distance runners to their altitude training, there is little scientific or historical evidence that training at altitude is superior to raining at sea level for improvements in VO2max or sea level performance. Historically, the best U.S. distance runners (with the exception of a few) have been born, lived and trained at sea-level. If altitude were a key ingredient for success, there would be a disproportionate percentage of elite U.S. distance runners coming from altitude compared to the percentage of people in the U.S. who live there. In my study on the training characteristics of the 2004 U.S. Olympic Marathon Trials qualifiers, I found that only 24 percent of men and 16 percent of women trained at altitude, and did so only because they resided there. More tellingly, there was no difference in marathon performance between athletes who trained at altitude and those who didn`t. The autor explains - the physiology of altitude, - the necessity to adjust running pace to altitud, - training responses to altitude, gives recommendations for training at altitude intensity and for competing at altitude.